Ultrafast dynamics in tailored VCSEL cavity geometry toward high-efficiency physical random number generation - Hang Lu; Omar Alkhazragi; Heming Lin; Tien Khee Ng; Boon Ooi (APL Photonics)
Ultrafast chaotic dynamics in lasers are essential for generating high-speed, high-entropy random signals, which is critical for advancing cryptography, secure communication, and emerging photonic technologies. In this study, for the first time, we explored how cavity geometry impacts chaotic dynamics in vertical-cavity surface-emitting lasers (VCSELs) to optimize their performance as high-efficiency entropy sources. By comparing circular, D-shaped, and pentagonal cavity designs, we demonstrate that the pentagonal geometry significantly enhances multimode interactions by introducing more modes overlapping in the space and spectrum, thereby driving strong mode competition and ultrafast chaotic lasing dynamics, which allow for an ultra-high-speed random number generation (RNG) rate of 800 Gb/s with minimal post-processing, approaching the physical limits of measurement systems. Furthermore, the pentagonal VCSEL exhibits an 85% increase in optical power density over conventional circular designs, combining high efficiency and compactness for scalable, secure, ultrafast communications. In addition, the D-shaped cavity exhibits a 65% increase in power compared to circular VCSEL with the most stable emission among the shapes investigated; hence, it is suitable for applications requiring high-power and steady output. Our findings also highlight the disruptive potential of tailored VCSEL cavity geometries for next-generation low-coherence light sources and advanced photonic technologies.